DAMPAK COVID-19 TERHADAP IMPLEMENTASI PEMBELAJARAN BAHASA INGGRIS SECARA MANDIRI DALAM PERKULIAHAN JARAK JAUH (DARING) DI TINGKAT PERGURUAN TINGGI - Nur Amalia Solikhah; Suripah . (Institut Pendidikan Tapanuli Selatan, 2021)
The aim of the study is to identify the implementation of self-distance learning (online) for university students due to the COVID-19 pandemic. This research uses library research wherein collecting data information with documentation techniques that are looking for data about relevant matters from various sources in the library such as documents, books, magazines, news. The criteria for the articles and news have chosen were discussion of the impact of COVID-19 and online learning at the tertiary level. From the resources obtained, the most relevant were selected and 15 journals and books items were selected. The results in the study show that the impact of COVID-19 on the implementation of online learning in tertiary institutions can be carried out quite well. This can be seen from the results of data from the journals and books which show that the impact of COVID-19 on the implementation of English self-distance learning (online) in Higher Education can be carried out properly and effectively during learning at home.